Effects of flooding on lead and cadmium speciation in sediments from a drinking water reservoir - Chrastný, V; Komárek, M; Tlustos, P; Svehla, J (Environmental monitoring and assessment, 2006)
Rímov water reservoir on the river Malse is the main source of drinking water for the town of Ceské Budejovice and for the majority of inhabitants in the South Bohemian region, Czech Republic. Changes in cadmium and lead contents in bottom sediments before and after an extensive flood on the river Malse in August, 2002 were therefore determined. A five-step sequential extraction procedure was used in order to obtain more detailed information about the influence of the flood on heavy metal retention. In order to determine the mobility of lead and cadmium, the mobility factor (MF) for these heavy metals was calculated. The mobility factor of cadmium showed a significant decrease in the upper parts of the sediment profiles after the flood (e.g., from 59.4% to 49.1%) caused by a release of cadmium especially from the exchangeable fraction. There were no significant changes in the lead mobility factor after the flood, but a decrease of lead concentration in the exchangeable fraction was observed. Presented results show that the flood led to a leaching of the heavy metals present in bottom sediments into the environment.
Keywords: Chemical Fractionation; kadmium; Rivers; geologické sedimenty; zásobování vodou; Water Pollutants, Chemical; Water Supply; Cadmium; řeky; Disasters; Česká republika; Lead; katastrofy; olovo; chemická frakcionace; Geologic Sediments; chemické látky znečišťující vodu; Czech Republic